ENVIRONMENTAL PERFORMANCE AS A MEDIATOR BETWEEN CHIEF EXECUTIVE OFFICER CHARACTERISTICS AND FINANCIAL PERFORMANCE - Ramadianti, Salsa Shabrina; Romli, Romli (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
The food and beverage manufacturing subsector faces increasing environmental pressure due to intensive resource use, waste generation, and rising stakeholder demands for sustainable practices. In this context, financial performance cannot be explained solely by managerial characteristics without considering environmental mechanisms. This study examines whether environmental performance mediates the relationship between CEO characteristics—specifically STEM educational background and female leadership—and financial performance. Drawing on upper echelon theory and stakeholder theory, the study investigates 50 purposively selected food and beverage companies listed on the Indonesia Stock Exchange during 2020–2024. Data were analyzed using path analysis and the Sobel test. The findings indicate that STEM CEOs do not significantly affect financial performance, whereas female CEOs and environmental performance have significant positive effects. Moreover, environmental performance mediates the influence of both STEM and female CEOs on financial performance. This study contributes by positioning environmental performance as a key explanatory mechanism that clarifies how CEO characteristics translate into financial outcomes in environmentally sensitive industries